The governors of school markets? Local education authorities, school choice and equity in Finland and Sweden. (December 2018) - Varjo, Janne; Lundström, Ulf; Kalalahti, Mira
As one of the key elements of the Nordic welfare model, education systems are based on the idea of providing equal educational opportunities, regardless of gender, social class and geographic origin. Since the 1990s, Nordic welfare states have undergone a gradual but wide-ranging transformation towards a more market-based mode of public service delivery. Along this trajectory, the advent of school choice policy and the growing variation in the between-school achievement results have diversified the previously homogenous Nordic education systems. The aim of our paper is to analyse how Finnish and Swedish local education authorities comprehend and respond to the intertwinement of the market logic of school choice and the ideology of equality. The data consist of two sets of in-depth thematic interviews with staff from the local providers of education, municipal education authorities . The analysis discloses the ways in which national legislation has authorized municipal authorities to govern the provision of education.